1996
DOI: 10.1159/000154800
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Renal Brush-Border and Basolateral Membrane Transporters for Organic Cations

Abstract: The renal proximal tubule is the site of active secretion of a diverse array of organic cations and bases (collectively, OCs). The basolateral entry step in transtubule OC transport involves an electrogenic facilitated diffusion process. OC exit into the tubule lumen is the active step in secretion and involves the carrier-mediated exchange of OC for H+. The specificity of these two processes is influenced less by steric characteristics of substrates than by their chemical lipophilicity, with both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Finally, the EC50 values for cimetidine and choline at the HV organic cation exchanger of the luminal mem brane of proximal tubules were reported to be 0.07 [7] and 21 mM [12], respectively, which is identical to the results found in our study (0.05 mM for cimetidine and 20 mM for cho line). The HVorganic cation transport system is electroneutral [1,3]; thus, uptake of ASP+ via this system should be independent of membrane voltage. As demonstrated here cell depolarization caused no change in cellular pH: however, it decreased the ASP+ accumu lation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the EC50 values for cimetidine and choline at the HV organic cation exchanger of the luminal mem brane of proximal tubules were reported to be 0.07 [7] and 21 mM [12], respectively, which is identical to the results found in our study (0.05 mM for cimetidine and 20 mM for cho line). The HVorganic cation transport system is electroneutral [1,3]; thus, uptake of ASP+ via this system should be independent of membrane voltage. As demonstrated here cell depolarization caused no change in cellular pH: however, it decreased the ASP+ accumu lation.…”
Section: Discussionmentioning
confidence: 99%
“…Three different transporters for organic cat ions have been identified in the proximal tubule so far [1][2][3]. An electrogenic organic cation transporter was identified in the basolateral membrane of this nephron segment [4][5][6], whereas in the luminal membrane two dif ferent transporters have been reported, an clcctroneutral HVorganic cation exchanger and an electrogenic choline transporter [7][8][9][10], Transport via these proteins is influenced by several cationic substrates inducing flux coupling phenomena such as cis-inhibition, trans-stimulation and trans-inhibition [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of lamivudine was found to inhibit the transient increase in TEA uptake. The uptake of TEA by BBMV under an outward H gradient is known to be mediated by an H aorganic cation anti-port system (Takano et al 1984;Wright 1996;Pritchard & Miller 1997), indicating that lamivudine might inhibit transport of organic cations by the anti-port system. As found previously, the stimulated uptake of TEA by BBMV under an outward H gradient was reduced signi®cantly by cimetidine, a representative cationic drug, but not by probenecid, a representative anionic drug (Takano et al 1985;Grif®ths et al 1992).…”
Section: Takatoshi Takubo Et Almentioning
confidence: 99%
“…At an early stage this uptake was reduced by lamivudine. TEA uptake by BLMV was reported to involve a carrier-mediated system and it was suggested that lamivudine might inhibit transport of organic cations by this system (Takano et al 1984;Wright 1996;Pritchard & Miller 1997). The uptake of TEA by BLMV at an early stage was reduced signi®cantly by the presence of cimetidine or trimethoprim; the IC50 of trimethoprim was fourfold (approx.)…”
Section: Takatoshi Takubo Et Almentioning
confidence: 99%
See 1 more Smart Citation